2019
DOI: 10.1016/j.trf.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

How speed and visibility influence preferred headway distances in highly automated driving

Abstract: While the introduction of highly automated vehicles promises lower accident numbers, a main requirement for wide use of these vehicles will be the acceptance by drivers. In this study a crucial variable for the acceptance of highly automated vehicles, the vehicle to vehicle distance expressed in time headway, was researched in a driving simulator. Research has shown that time headway distances, perceived as comfortable in self-driving and assisted driving with adaptive cruise control, remain constant over a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…It is used to describe the characteristic of the driver in dense fog environment as to follow the AGV within the scope of visibility and keep safety distance from the AGV. e simulation results show that the phenomenon shown in the simulation is consistent with the assumptions of HDV driver characteristics and fall into the relationship of speed and visibility as studied by Siebert and Wallis [45]. irdly, the distributed serial model predictive control (DMPC) model is used to control the fleet in dense fog environment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It is used to describe the characteristic of the driver in dense fog environment as to follow the AGV within the scope of visibility and keep safety distance from the AGV. e simulation results show that the phenomenon shown in the simulation is consistent with the assumptions of HDV driver characteristics and fall into the relationship of speed and visibility as studied by Siebert and Wallis [45]. irdly, the distributed serial model predictive control (DMPC) model is used to control the fleet in dense fog environment.…”
Section: Discussionsupporting
confidence: 72%
“…From the phenomena shown in Figures 4 and 5, they are consistent with the assumptions of HDV driver characteristics discussed above and falls into the relationship of speed and visibility as studied by Siebert and Wallis [45]. erefore, the proposed car-following model above can effectively describe the driver behavior within dense fog environment in the fleet control.…”
Section: E Ca-based Nasch Car Following Model Verificationsupporting
confidence: 81%
See 1 more Smart Citation
“…Few studies deal with driving parameters, which are mostly conducted on a simulator. However, the parameters evaluated were varied: driving style (Techer et al, 2019;Hartwich et al, 2018;Mühl et al, 2019;Oliveira et al, 2019), driving behaviour (time headway, lateral offset, quality of driving; Siebert & Wallis, 2019;Voß et al, 2018;Walker et al, 2019). These studies highlighted the crucial role of the conditions such as road type, time pressure, traffic volume, visibility, weather, other vehicle behaviour, presence of explanations or side of the seat in the evaluation (Frison et al, 2019;Wintersberger et al, 2019), indicating the need to multiply studies to investigate combinations of conditions.…”
Section: Iii33 Preferencesmentioning
confidence: 99%
“…We register drivers subjective experience through three items of the disco-scale [18], assessing perceived control, ability to intervene, and perceived responsibility for potential accidents. We further investigate driver behaviour, by comparing headways assumed in manual driving to headways assumed under manoeuvre control driving conditions, building on research that has identified a high inter-individual variance in time headways [19,20] and a need for adjustable headways in highly automated driving [21]. Parts of this study have been reported in a previous paper [22].…”
Section: Introductionmentioning
confidence: 99%